microRNA-145-5p inhibits prostate cancer bone metastatic by modulating the epithelial-mesenchymal transition - Luo, Bingfeng; Yuan, Yuan; Zhu, Yifei; Liang, Songwu; Dong, Runan; Hou, Jian; Li, Ping; Xing, Yaping; Lu, Zhenquan; Lo, Richard; Kuang, Guan-Ming (Frontiers in Oncology, 2022)
Objective To investigate the effects of miRNA-145-5p on the tumor development and progression of prostate cancer (Pca) bone metastasis. Methods Levels of miRNA-145-5p were assessed by real-time quantitative PCR in PC3 (bone metastatic Pca cells), 22RV1 (non-metastatic Pca cells), RWPE-1 (non-cancerous prostate epithelial cells) and Pca tissues collected from patients with and without bone metastases. The impact of miRNA-145-5p on cell proliferation was tested by CCK8 assay, colony formation assay and flow cytometric cell cycle analysis. Effects on invasion and migration of PC3 cells were determined by Transwell and wound healing assays. Western blotting, enzyme-linked immunosorbent assay, and flow cytometry apoptosis analyses were also performed to assess roles in metastasis. Results Levels of miRNA-145-5p were decreased in Pca bone metastases and miRNA-145-5p inhibited cell proliferation, migration and invasion. miRNA-145-5p inhibited the expression of basic fibroblast growth factor (bFGF), insulin-like growth factor (IGF) and transforming growth factor-β (TGF-β) in PC3 cells. miR-145-5p increased the expression of the epithelial marker E-cadherin and reduced the expression of matrix metalloproteinase 2 and 9 (MMP-2 and MMP-9). It was found that miRNA-145-5p mediated the epithelial-mesenchymal transition (EMT) and induced apoptosis. Conclusions miRNA-145-5p negatively regulated the EMT, inhibited Pca bone metastasis and promoted apoptosis in Pca bone metastasis. Mimicry of miRNA-145-5p action raises the possibility of a novel target for treating Pca with bone metastases.